2015
DOI: 10.1590/1516-635x170169-76
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary phytase on broiler performance and digestive, bone, and blood biochemistry characteristics

Abstract: Antagonism, digestible amino acid, egg components, Haugh units. ABSTRACTThe dietary inclusion of phytase increases nutrient and energy bioavailability for broilers. The effect of phytase increases nutrients and energy bioavailability for either the objective of this experiment was to evaluate the influence of nutrient and energy reduction in diets supplemented with phytase on the performance, gastrointestinal pH, organ and bone composition, and blood biochemistry of broilers between eight and 21 days of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
4
18
0
1
Order By: Relevance
“…Study conducted by WANG et al (2013) did not observe such fact. However, SOUSA et al (2015), upon evaluating diets with reduced nutritional levels, in the presence or absence of phytase, observed an increase in the relative weight of the heart, but with the absence of phytase. Authors noted that cardiac hypertrophy may be caused by hypophosphatemia due to the low supply of phosphorus.…”
Section: ----------Phytase (Ftu Kg -1 )----------------P-value For Thmentioning
confidence: 96%
See 2 more Smart Citations
“…Study conducted by WANG et al (2013) did not observe such fact. However, SOUSA et al (2015), upon evaluating diets with reduced nutritional levels, in the presence or absence of phytase, observed an increase in the relative weight of the heart, but with the absence of phytase. Authors noted that cardiac hypertrophy may be caused by hypophosphatemia due to the low supply of phosphorus.…”
Section: ----------Phytase (Ftu Kg -1 )----------------P-value For Thmentioning
confidence: 96%
“…Phytase has an effect on performance, retention and availability of nutrients, reducing the variability of energy from feed stuffs, neutralizing the anti-nutritional effects of phytate; thus, increasing the accuracy of feed formulation (SOUSA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shirley and Edward (2003) found that supplementing phytase from 0 to 12000 U/kg significantly increased body weight gain from 287 to 515 g/chick [35]. De Sousa et al (2015) reported that broilers fed on the phytase supplemented diet showed 4.40, 11.04 and 7.14% (P < 0.05) improvement in feed intake, weight gain and feed conversion ratio, respectively [36]. Moreover, Lim et al (2001) in a study demonstrated that inclusion of phytase in feed increased weight gain and reduced mortality [37].…”
Section: Effect Of Agpp-p Phytase Supplementation On Digestibility Anmentioning
confidence: 99%
“…Как следствие, благодаря фитазе улучшается переваримость протеина и использование аминокислот корма, снижаются эндогенные потери аминокислот (33). Также сообщается об улучшении минерализации костяка цыплят под влиянием фитаз (34)(35)(36), что отмечалось и в наших опытах.…”
Section: значения индексов биоразнообразия микроорганизмов в слепых оunclassified